Literacy as gendered discourse : engaging the voices of women in global societies - Williams Ntiri, Daphne (Adult education special topics., 2015)
This volume continues IAP's dedication to the diverse field of international adult learning in the tradition of those books related to the We Learn and AAHE conferences. It is an edited and refereed collection and part of the larger body of scholarly publications associated with professional organizations such as AAACE, MAACE, We Learn, Women Studies Association, African Studies Association, Gender Studies Association and Global Studies network.Literacy as gendered discourse is important because it fills a unique niche in the canon of studies that investigate the challenges and prevailing norms associated with women and literacy studies, adult learning and development. It also offers a current volume for scholars and practitioners based on both research and practice-based research. This collection is appropriate for a wide variety of professors, researchers, practitioners, and students in the field of adult literacy studies, women/gender and development studies.In order to create this valuable contribution to the literacy and women's studies literature, international scholars have contributed their research in which they study and explore the lives of women in various countries. Their work establishes findings that help to illuminate and analyze the different manifestations of women's global experiences through the unique lens of local respondents or through their own lens as academic researchers. In these ways the results provide powerful insight and useful lessons applicable to the fields of gender study, women's studies, adult literacy, development studies, international studies, etc.